Metagenomic Next-Generation Sequencing vs. Traditional Pathogen Detection in the Diagnosis of Infection After Allogeneic Hematopoietic Stem Cell Transplantation in Children - Qu, Yuhua; Ding, Wenjiao; Liu, Sha; Wang, Xiaojing; Wang, Pengfei; Liu, Haiyan; Xia, Han; Chen, Yong; Jiang, Hua (Frontiers in Microbiology, 2022)
We compared metagenomic next-generation sequencing (mNGS) and traditional pathogen detection in investigating the pathogens of infections (such as bloodstream infections, pulmonary infections, and central nervous system (CNS) infections) in pediatric allo-HSCT recipients. This study retrospectively analyzed 101 pediatric recipients of allo-HSCT, including 54 bronchoalveolar lavage fluid samples, 32 blood samples, and 15 cerebrospinal fluid samples. Eighty-seven were diagnosed with post-transplant infectious diseases and 14 with non-infectious diseases eventually. The sensitivity and specificity of mNGS were compared to traditional pathogen detection methods. mNGS was more sensitive (89.7%) compared to conventional pathogen detection (21.8%), with a difference of 67.9% (P<0.001), However, mNGS was less specific (78.5%) than traditional methods (92.9%), with a difference of 14.4% (P=0.596). The sensitivity of mNGS for diagnosing pulmonary infections, bloodstream infections or viremia, and CNS infections post-transplant were 91.7%, 85.7%, and 90.9%, respectively. In contrast, the sensitivity of conventional testing for diagnosing pulmonary infections, bloodstream infections or viremia, and CNS infections post-transplant were 22.9%, 21.4%, and 18.2%, respectively. There were significant differences in the sensitivity of mNGS and conventional testing in BALF, blood, and CSF samples, with P values of 0.000, 0.000, and 0.002, respectively. Among the patients with pulmonary infections, the percentage with the mNGS-positive result was 44/48 (91.7%), included viruses (n = 12), bacteria (n = 17), fungi (n = 9), and mixed infections (n=6). Among the patients diagnosed with fungal pneumonia (n=9), the most prevalent pathogenic fungi were Pneumocystis Jiroveci (n=6), which were also detected in 4 patients with mixed infectious pneumonia. Of the 15 CSF specimens enrolled, 11 patients were eventually diagnosed with CNS infections. Ten pathogens were identified by mNGS in 11 patients, including viruses (n = 8), bacteria (n = 1), and fungi (n = 1). These results suggest that mNGS might be a promising technology for diagnosing infections post HSCT in children. Pneumocystis Jiroveci was the most frequent pathogen of pulmonary infections post-transplant, while viruses were the most common pathogens of CNS infections in allo-HSCT recipients.